2015
DOI: 10.1016/j.athoracsur.2015.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Versus Bilateral Antegrade Cerebral Protection During Aortic Surgery: An Updated Meta-Analysis

Abstract: Unilateral versus bilateral ASCP administration did not result in different mortality and neurologic morbidity rates. Nevertheless, among prolonged CA times unilateral ASCP resulted in poorer outcomes with respect to bilateral ASCP. Furthermore, moderate hypothermia was associated with best outcomes in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 15 publications
8
66
0
1
Order By: Relevance
“…[1][2][3] Currently, 3 different cerebral protection strategies are available: isolated deep hypothermic circulatory arrest (DHCA), circulatory arrest coupled with retrograde cerebral perfusion (RCP), and circulatory arrest coupled with antegrade cerebral perfusion (ACP). The advantages and disadvantages of these cerebral protection techniques have been extensively studied, [4][5][6][7][8][9][10][11] but consensus on the optimal strategy is still lacking. Over the past 15 years, 8 meta-analyses have reported pairwise comparisons of DHCA, RCP, and ACP in different combinations.…”
Section: Perspectivementioning
confidence: 99%
“…[1][2][3] Currently, 3 different cerebral protection strategies are available: isolated deep hypothermic circulatory arrest (DHCA), circulatory arrest coupled with retrograde cerebral perfusion (RCP), and circulatory arrest coupled with antegrade cerebral perfusion (ACP). The advantages and disadvantages of these cerebral protection techniques have been extensively studied, [4][5][6][7][8][9][10][11] but consensus on the optimal strategy is still lacking. Over the past 15 years, 8 meta-analyses have reported pairwise comparisons of DHCA, RCP, and ACP in different combinations.…”
Section: Perspectivementioning
confidence: 99%
“…This precluded further analyses and the possibility to evaluate these surgical strategies as an additional measure of the quality of care in TAD patients, although arterial cannulation strategies and cerebral protection strategies have been proved to influence operative outcomes in aortic surgery. 70,71 The systematic review was limited in that it relied on the reported information on confounding variables that were controlled for; consistent analyses of all studies can be done only when data on individual patients are combined. Many of the included studies were at risk of bias, and there was substantial heterogeneity in many of the effect estimates.…”
Section: Low Volume or 95%ci Weight Weight Odds Raɵo (95%ci) Studymentioning
confidence: 99%
“…Current cerebral protection techniques use systemic hypothermia alone or in combination with adjunctive cerebral perfusion; however, strategies differ with regard to the degree of hypothermia and the method of cerebral perfusion (antegrade versus retrograde). In this issue of The Annals, Angeloni and colleagues [1] seek to determine the optimal method of delivering antegrade cerebral perfusion. The authors provide an update of their previous meta-analysis of data examining outcomes of arch reconstruction using unilateral (uASCP) or bilateral antegrade selective cerebral perfusion (bASCP) [2].…”
Section: Invited Commentarymentioning
confidence: 99%